A Case Study on Stress Management in Modern Scenario - T. Sobha Rani, L. Prathiba, E. Sravanthi (Mathematical Statistician and Engineering Applications, 2023)
Stress is a psychological and corporeal response of the body that occurs whenever we must acclimatize to altering circumstances, whether those conditions are real or perceived, positive or negative, although everyone has stress in their lives, people respond to stress in different ways. Some people seem to be sternly exaggerated while others seem calm, cool, and collected all the time.Stress is an unbearable state of emotional and physiological stimulation that people experience in situations that they recognize as dangerous or threatening to their wellbeing. Stress is a common experience. We may feel stress when we are very busy, have important deadlines to meet, or have too little to finish all our tasks. Often people are facing experience stress because lot of problems Occurred work place and social relationships. Hence this paper will examine the different symptoms and behavior due to cause of Stress at workplace.